El cambio de paradigma en la comparación forense de voz en el Perú: avances y una revisión preliminar - Jimenez Peña, Jhon (2025)
The purpose of this paper is to preliminarily present the status of the paradigm shift or new paradigm in forensic voice comparison in Peru. First, the ambiguous terminology (such as forensic acoustics, voice identification or forensic phonoaudiology as forensic voice comparison) used to avoid its inappropriate use in academic and judicial situations is reviewed. Second, forensic phonetics and its areas of practice are presented in general terms. Third, the methodological approaches in voice comparison and the way of expressing the results are presented and it is explained why the forensic expert in voice comparison should opt for the analysis and results through the likelihood ratio. Fourth, the basis of the paradigm shift and its influence on forensic voice comparison is discussed in depth. Fifth, the current state of research in forensic voice comparison in Peru is presented. As a result of this research, it can be argued that the current studies demonstrate a transition towards a paradigm shift, especially through the use of automated programs.